DEVELOPMENT OF THE COMPOSITION OF ARTIFICIAL GRANITE STONE BUILDING MATERIAL USING EARTH’S MOUNTAIN RESOURCES - Yesbosinov , Maxmud Perdebayevich (GOLDEN BRAIN, 2024)
The development of artificial granite stone building materials presents an innovative approach to sustainable construction by leveraging natural resources from the Earth’s mountains. This study explores the composition, properties, and potential applications of artificial granite, aiming to create a durable, aesthetically pleasing, and environmentally friendly building material. By utilizing mountain resources, we aim to reduce environmental impact while meeting the high demand for granite in the construction industry.